Evaluation of asphalt and asphalt mixtures' water stability method under multiple freeze-thaw cycles. (20th December 2019) - Wu, Haonan; Li, Ping; Nian, Tengfei; Zhang, Guohong; He, Teng; Wei, Xiying
Highlights: Four types of adhesion evaluation methods were used to study three kinds of asphalts under multiple freeze-thaw cycles. The three kinds of asphalts' adhesion and the asphalt-aggregates' degree of adhesion were analyzed under multiple freeze-thaw cycles. The water stability and water permeability coefficients of different grades of asphalt mixtures were subjected to multiple freeze-thaw cycles. The correlation between the evaluation index corresponding to the four adhesion evaluation methods and the water stability index was evaluated by grey relation entropy analysis. Abstract: Asphalt pavement was widely used in various road construction due to its comfortable driving, low vibration, low noise and convenient maintenance. However, during the service of asphalt pavement, the water in the pavement produced a freeze-thaw cycle due to the change of temperature, which caused a large number of early diseases on the pavement. In order to explore a proper water stability evaluation method for asphalt and asphalt mixture. In this paper, four kinds of adhesion evaluation methods were used to analyze and compare three kinds of asphalt under multiple freeze-thaw cycles. The water stability and water permeability coefficient of the asphalt mixture of three kinds of asphalt under different grading types were tested after multiple freeze-thaw cycles. The correlation degree between the adhesion evaluation index and the water stability index was evaluated by the grey relation entropy analysis theory. The results show that the method of evaluation of photoelectric colorimetry and water immersion combined, or the method of evaluation of photoelectric colorimetry and contact angle combined evaluate asphalt and aggregate's adhesion is recommended. The research results are of great significance for evaluating the water stability of asphalt and asphalt mixtures.